Pengaruh Produk, Harga, Dan Promosi Terhadap Keputusan Pembelian Smartphone Dengan Lokasi Sebagai Variabel Intervening Pada Alun Cell di Desa Kota Baru Lampung Tengah - Nina Lelawati; Suwarto; Deska Saputra (Jurnal Manajemen DIVERSIFIKASI, 2025)
This research aims to determine the influence of products, prices and promotions on smartphone purchasing decisions based on locations in Alun Cell, Kota Baru, Central Lampung. Quantitative descriptive research method, non-probability sampling technique using accidental, the respondents were 96 Alun Cell consumers. The results of the research show that there is a direct influence of products on purchasing decisions, there is a direct influence of price on purchasing decisions, there is a direct influence of promotion on purchasing decisions, there is a direct influence of products on location, there is a direct influence of promotion on location, and there is a direct influence of location on purchasing decisions smartphones.